2014
DOI: 10.2106/jbjs.m.00941
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Concentric and Eccentric Glenospheres in Reverse Shoulder Arthroplasty

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…In the patients, the mean PSNA, PGRD, and inferior overhang were 92°, 21.2 mm, and 4.3 mm, respectively. Poon et al 15) suggested that more than 3.5 mm of inferior overhang could prevent notching; however, there were no differences in the incidence of notching or clinical results between concentric and eccentric glenospheres. In our study, the 5.8 mm eccentric glenosphere with 15° of inferior tilt could reduce the incidence of notching, but grade 1 notching occurred in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients, the mean PSNA, PGRD, and inferior overhang were 92°, 21.2 mm, and 4.3 mm, respectively. Poon et al 15) suggested that more than 3.5 mm of inferior overhang could prevent notching; however, there were no differences in the incidence of notching or clinical results between concentric and eccentric glenospheres. In our study, the 5.8 mm eccentric glenosphere with 15° of inferior tilt could reduce the incidence of notching, but grade 1 notching occurred in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Roche and colleagues 14 reviewed the radiographs of 151 patients who underwent primary reverse TSA at a mean follow-up of 28.3 months postoperatively; they found that 13.2% of their patients had a notch and that, on average, their patients who had no scapular notch had significantly more inferior glenosphere overhang than those who had a scapular notch. Poon and colleagues 15 found that a glenosphere overhang of >3.5 mm prevented notching in their randomized control trial comparing concentrically and eccentrically placed glenospheres. Multiple other studies have demonstrated similar results and recommended inferior glenoid translation and inferior glenoid inclination to avoid scapular notching.…”
Section: Glenosphere Placementmentioning
confidence: 99%
“…With innovations in reverse implant design and improvements in surgical technique, the occurrence of notching has decreased. Poon et al performed a randomized controlled trial comparing the results of concentric and eccentric glenospheres in reverse shoulder arthroplasty 24 . The surgical technique for both groups involved the placement of the glenoid baseplate flush with the inferior glenoid rim.…”
Section: Shoulder Arthroplastymentioning
confidence: 99%